Hukum Islam Dalam Memaknai Sebuah Perbedaan - Hermanto, Agus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Islam is a religion rahmatan lil'alamin, for that Islam can put the situation and conditions. Islam is the religion HanÄ«f, fairness and tolerance to their ikhtilaf (dissent). In terms of the causes and roots, there are two forms ikhtilaf (dispute), the deviation caused by the character and thought. Unjustified deviation is a deviation in aqidah matter of principle. Deviation is actually a little touch on the basic framework of worship. However, when the jurists began to enter the technical and operational principle that no deviation is irreversible appearance. Deviation can be justified is the deviation in trouble furu', and the issue is not the principle I'tiqad. Deviation different from the iftiraq, iftiraq according to the language comes from the word meaning mufarawah division and separation. Meanwhile, according to the terms of the scholars, iftiraq is out of the Sunnah and Jama'ah on one ushul (principal) of a judge actions ushul fundamental, both in aqidah or amaliyah.